Integration of sexually transmitted infection and HIV pre-exposure prophylaxis services in sub-Saharan Africa: a scoping review - Anand, Priyanka; Wu, Linxuan; Mugwanya, Kenneth (Frontiers in Reproductive Health, 2023)
Background Persons living in sub-Saharan Africa (SSA) face disproportionate risk from overlapping epidemics of HIV and bacterial sexually transmitted infections (STIs). Pre-exposure prophylaxis (PrEP) for prevention is gradually being scaled up globally including in several settings in SSA, which represents a key opportunity to integrate STI services with HIV pre-exposure prophylaxis (PrEP). However, there is limited literature on how to successfully integrate these services, particularly in the SSA context. Prior studies and reviews on STI and PrEP services have largely focused on high income countries. Methods We conducted a scoping review of prior studies of integration of STI and PrEP services in SSA. We searched PubMed, EMBASE, Cochrane, and CINAHL, in addition to grey literature to identify studies that were published between January 2012 and December 2022, and which provided STI and PrEP services in SSA, with or without outcomes reported. Citations and abstracts were reviewed by two reviewers for inclusion. Full texts were then retrieved and reviewed in full by two reviewers. Results Our search strategy yielded 1951 records, of which 250 were retrieved in full. Our final review included 61 reports of 45 studies. Most studies were conducted in Southern (49.2%) and Eastern (24.6%) Africa. Service settings included public health clinics (26.2%), study clinics (23.0%), sexual and reproductive care settings (23.0%), maternal and child health settings (8.2%), community based services (11.5%), and mobile clinics (3.3%). A minority (11.4%) of the studies described only syndromic STI management while most (88.6%) included some form of etiological laboratory STI diagnosis. STI testing frequency ranged from baseline testing only to monthly screening. Types of STI tested for was also variable. Few studies reported outcomes related to implementation of STI services. There were high rates of curable STIs detected by laboratory testing (baseline genitourinary STI rates ranged from 5.6–30.8% for CT, 0.0–11.2% for GC, and 0.4–8.0% for TV). Discussion Existing studies have implemented a varied range of STI services along with PrEP. This range reflects the lack of specific guidance regarding STI services within PrEP programs. However, there was limited evidence regarding implementation strategies for integration of STI and PrEP services in real world settings.